A video annotation learning approach to improve the effects of video learning. Issue 4 (4th July 2018) - Chiu, Po-Sheng; Chen, Hsin-Chin; Huang, Yueh-Min; Liu, Chia-Ju; Liu, Ming-Chi; Shen, Ming-Hsun
ABSTRACT: Digital video has become a popular instructional media, which makes students more enthusiastic about the subjects they are learning. However, students may not be able to receive these benefits if the videos present the information they contain too quickly. To overcome this problem, this study proposed a video annotation learning system, by which learners can annotate and highlight the interesting or important contents to make them more memorable. A quasi-experiment was conducted on a cardiopulmonary resuscitation course to evaluate the effectiveness of the proposed learning approach. Eye-tracking technology was used to examine students' learning process, and assess whether the use of annotations increased their attention. The findings reveal that the proposed approach could encourage students to concentrate more on the critical parts of the instructional video, and thus resulted in better learning performance than the conventional approach to using videos.